Wife battering from an Islamic perspective and Malaysian legal provisions - Hussin, Nasimah; Wan Muhammad, Ramizah (International Islamic University Malaysia, 2008)
Wife battering is a ground for divorce in the Malaysian Shariah Courts. Some husbands claim that it is their prerogative right to discipline their wives by corporal punishment based on their superficial understanding of the Qur’anic text 4:34 which seems to justify this argument. Some feminist organizations condemn this and allege that if physical assault is lawful in Islam, it leads to a woman’s persecution. This paper examines the issue of wife battering from both Islamic perspective and Malaysian legal provisions. It clarifies the misconception that exists regarding the above issue which is in fact, due to lack of understanding and prejudice against Islamic law.